Characterization and comparison of metaproteomes in traditional and commercial dajiang, a fermented soybean paste in northeast China. (15th December 2019) - Xie, Mengxi; An, Feiyu; Yue, Xiqing; Liu, Yiming; Shi, Haisu; Yang, Mei; Cao, Xueyan; Wu, Junrui; Wu, Rina
Highlights: Comparative metaproteome of traditional and commercial dajiang was performed. It firstly reveals the dynamic changes of enzymes involved in main metabolism pathways in dajiang. Penicillium, Tetracoccus and Bacillus in traditional dajiang contributed to the formation of flavor. Traditional dajiang fermentation may have greater food safety hazards than commercial dajiang. Abstract: Dajiang is a popular Chinese fermented soybean condiment. Here, a comparative metaproteomic analysis of traditional and commercial dajiang was performed during fermentation. A total of 4250 and 1421 peptide sequences were obtained from 3493 and 1987 proteins in traditional and commercial dajiang, respectively. 4299 differentially expressed microbial proteins show a high metabolic heterogeneity between the two types of dajiang. The KEGG annotation indicated that there were some pathways related to human diseases, which suggest that some microbes in traditional dajiang fermentation may have greater food safety hazards. In combination with qualitative metabolomic analysis, we further traced metabolic intermediates and key enzymes in several main fermentation pathways of dajiang to be mainly affiliated with Penicillium, Tetracoccus and Bacillus in traditional samples, as well as Aspergilus in commercial samples. These results could provide information for the selection of strains that are more suitable to produce high quality dajiang and other fermented products.